Evaluation of molybdenum tailings as replacement for fine aggregate in concrete: Mechanical, corrosion resistance, and pore microstructural characteristics. (8th August 2022) - Quan, Xiaoyi; Wang, Sheliang; Liu, Kangning; Xu, Jin; Zhao, Nan; Liu, Bo
Highlights: Molybdenum tailings by-product are used as fine aggregate in the development of concrete. The resistance to F-T cycles in water and Na2 SO4 solution was investigated. Nuclear magnetic resonance to analyze the pore structure characteristics is adopted. Visualization and quantitative analysis of pore evolution based on industrial CT technology. The relationship between porosity and the number of the F-T cycle was established. Abstract: This study explored the feasibility of molybdenum tailings (MTs) as an alternative to natural river sand for concrete production. Firstly, the compressive ( f cu ) and splitting tensile strengths ( f sts ) of molybdenum tailings concrete (MTs-C) and the relationship between the two were evaluated. Then, the corrosion resistance of MTs-C was investigated. This includes f cu loss, relative dynamic elastic modulus (RDEM) loss, and mass loss. Subsequently, the pore distribution under the sulfate freeze–thaw (F-T) cycle was tested by nuclear magnetic resonance (NMR). Besides, the pore evolution characteristics were visualized and quantified using industrial computed tomography (CT) techniques. Finally, the corrosion products were identified by X-ray diffraction (XRD). The results showed that the mechanical properties of concrete with 60% MTs only decreased by less than 10%. In the sulfate F-T environment, the corrosion resistance of MTs-C decreases as the replacement ratio of MTs increases, and it decreases significantly when the replacement ratio exceeds 60%. The porosity of MTs-C was the first to decrease and then increase with the F-T cycle, while the proportion of large pores gradually increased. Based on industrial CT scanning, it was further verified that the evolution of small pores to large pores is the main degradation mechanism of sulfate F-T cycles for the pore structure of MTs-C. Taking into account the mechanical properties, durability, and pore evolution, it was determined that 60% MTs replacement of natural sand for concrete production would be feasible.